2011
DOI: 10.1007/s11832-011-0365-z
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb motion analysis in children with hemiplegic cerebral palsy: Proximal kinematic changes after distal botulinum toxin or surgical treatments

Abstract: Purpose The purpose of this study is to describe the kinematic changes in children with cerebral palsy (CP) after treatments performed on the forearm, wrist or thumb, with specific attention to the changes around the trunk, shoulder and elbow kinematics. Methods With the use of a specific kinematic protocol, we first described the upper limb kinematics in a group of 27 hemiplegic patients during two simple daily tasks. Eight of these children were treated with botulinum toxin (Botox Ò , Allergan) injection or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
2
25
1
11
Order By: Relevance
“…In another study analyzing reaching movements of children with hemiplegic CP, abnormalities in proximal joint kinematics during a reach-to-grasp movement were larger than in a reach-to-hit movement that required less distal upper extremity control [30]. Also, treatment of distal muscle impairments with injection of botulium toxin or surgery was shown to improve proximal muscle control during functional tasks [31]. This influential effect of distal arm activity on proximal arm activity suggests that the act of grasping in our study may have caused compensatory proximal muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…In another study analyzing reaching movements of children with hemiplegic CP, abnormalities in proximal joint kinematics during a reach-to-grasp movement were larger than in a reach-to-hit movement that required less distal upper extremity control [30]. Also, treatment of distal muscle impairments with injection of botulium toxin or surgery was shown to improve proximal muscle control during functional tasks [31]. This influential effect of distal arm activity on proximal arm activity suggests that the act of grasping in our study may have caused compensatory proximal muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…Then, our protocol could be computed to monitor the evolution of upper limb kinematics in patients during rehabilitation, for example, when employing robot-assisted therapy, 6,13 constraint-induced movement therapy 31 and botulinum toxin. 8,9 Finally, a robot is an assessment tool but also a rehabilitation tool. Kinematic analyzes computed during robot-assisted therapy could enable the device to adapt the level of assistance provided to the patients in real time.…”
Section: Age Effects and Normative Values For Upper Limb Kinematicsmentioning
confidence: 99%
“…Previous studies have demonstrated the effects of age on upper limb kinematics in children aged from 3 to 18 years. 10, 24 Olivier et al 23 showed progress in upper limb kinematics over time by comparing children (age range in years: [6][7][8][9][10][11]) and young adults (mean age in years: 38). Finally, some studies have objectified the aging of upper limb kinematics by comparing young adults (age range in years: [20][21][22][23]) and the elderly (age range in years: [70][71][72][73][74][75][76][77][78][79][80]).…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional motion analysis (3DMA) provides a quantitative measurement of UL movement patterns of proximal and distal joints [19][20][21] , highlighting its added value compared to clinical scales 22 . Its utility and sensitivity to identify improvements at joint level after UL surgery and botulinum toxin injections has been shown 23,24 . These improvements were most obvious in the proximal joints (shoulder, scapula or trunk) for which clinical scales are less sensitive 23 .…”
Section: Introductionmentioning
confidence: 99%